Activation of NRF2 and ATF4 Signaling by the Pro-Glutathione Molecule I-152, a Co-Drug of N-Acetyl-Cysteine and Cysteamine - Rita Crinelli; Carolina Zara; Luca Galluzzi; Gloria Buffi; Chiara Ceccarini; Michael Smietana; Michele Mari; Mauro Magnani; Alessandra Fraternale (MDPI AG, 2021)
I-152 combines two pro-glutathione (GSH) molecules, namely N-acetyl-cysteine (NAC) and cysteamine (MEA), to improve their potency. The co-drug efficiently increases/replenishes GSH levels in vitro and in vivo; little is known about its mechanism of action. Here we demonstrate that I-152 not only supplies GSH precursors, but also activates the antioxidant kelch-like ECH-associated protein 1/nuclear factor E2-related factor 2 (KEAP1/NRF2) pathway. The mechanism involves disulfide bond formation between KEAP1 cysteine residues, NRF2 stabilization and enhanced expression of the γ-glutamil cysteine ligase regulatory subunit. Accordingly, a significant increase in GSH levels, not reproduced by treatment with NAC or MEA alone, was found. Compared to its parent compounds, I-152 delivered NAC more efficiently within cells and displayed increased reactivity to KEAP1 compared to MEA. While at all the concentrations tested, I-152 activated the NRF2 pathway; high doses caused co-activation of activating transcription factor 4 (ATF4) and ATF4-dependent gene expression through a mechanism involving Atf4 transcriptional activation rather than preferential mRNA translation. In this case, GSH levels tended to decrease over time, and a reduction in cell proliferation/survival was observed, highlighting that there is a concentration threshold which determines the transition from advantageous to adverse effects. This body of evidence provides a molecular framework for the pro-GSH activity and dose-dependent effects of I-152 and shows how synergism and cross reactivity between different thiol species could be exploited to develop more potent drugs.